An Assessment of the contribution of monetary unions to economic growth - MBEINTA, Lambert Chia (KDI School, 2018)
Monetary Unions (MU) as a form of economic integration is believed to procure a bonus growth point to member countries of the union. However, since Britain voted to leave the European Union in 2016, there are growing claims that integration does not enhance growth and welfare. This thesis examines the impact of MU membership on economic growth, with focus on the CFA Franc zone. The random effect model is used to analyze panel data from 47 SSA countries for the period 2000 to 2015. The result shows a negative and significant growth effect. Also, capital accumulation appears to be the main determinant of growth. These results remain unchanged when the pooled OLS regression is used. This implies that MU membership does not always enhance economic growth. These findings are similar to those of previous studies. Member countries should revisit the CFA Franc cooperation framework to foster growth and development within the region.
Thesis(Master) --KDI School:Master of Public Policy,2018